2014
DOI: 10.4068/cmj.2014.50.3.75
|View full text |Cite
|
Sign up to set email alerts
|

HDL-Associated Paraoxonase 1 as a Bridge between Postmenopausal Osteoporosis and Cardiovascular Disease

Abstract: The association of postmenopausal osteoporosis (PMOP) with both atherosclerosis and vascular/valvular calcification is well known. Recently, ample evidence has suggested a common etiologic factor, namely, reduced HDL-associated paraoxonase 1 (PON1) activity, as a causative factor in the development of PMOP and cardiovascular disease (CVD). This common etiologic factor not only contributes to atherosclerotic diseases but also to PMOP following an almost identical mechanism including dysfunctional HDL and lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The present study found a direct association between the CpG methylation at this locus and HDL-cholesterol levels; other recent studies found an association with diabetes (17,18). The complex interrelations between lipids, diabetes and arterial calcifications merit additional studies (19)(20)(21)(22), our data suggest that the low methylation level at this locus could be associated with higher PHOSPHO1 levels. This could induce calcification due to low HDL cholesterol levels and altered glucose homeostasis or other potential mechanisms.…”
Section: Discussionsupporting
confidence: 67%
“…The present study found a direct association between the CpG methylation at this locus and HDL-cholesterol levels; other recent studies found an association with diabetes (17,18). The complex interrelations between lipids, diabetes and arterial calcifications merit additional studies (19)(20)(21)(22), our data suggest that the low methylation level at this locus could be associated with higher PHOSPHO1 levels. This could induce calcification due to low HDL cholesterol levels and altered glucose homeostasis or other potential mechanisms.…”
Section: Discussionsupporting
confidence: 67%
“…The pathophysiology of HHcy-derived CVD in RA patients is largely uncharacterized. Nevertheless, indirect evidence from relevant observations in the general population together with the crucial role of inflammation push forward our understanding of the several derangements that may interact to cause or exacerbate it [ 6 , 11 , 12 , 14 , 21 , 22 , 36 38 , 44 51 ]. They include: i) oxidative stress [ 12 , 44 ] ii) chronic inflammation and immune activation [ 11 , 14 , 37 , 38 , 45 ] iii) propensity for a pro-atherogenic lipid profile [ 44 47 ] iv) poor disease status and severe radiological damage [ 6 , 12 , 38 , 44 ] v) thrombophilia [ 21 , 22 , 38 ] vi) increase of plasma ADMA levels [ 14 , 48 ] vii) osteoprotegerin [ 49 ] viii) genetic and epigenetic factors [ 36 , 50 , 51 ].…”
Section: Association Between Hyperhomocysteinemia and Cardiovascular mentioning
confidence: 99%
“…Furthermore, visceral obesity as a hallmark of MetS is associated with increased levels of adiponectin and reduced production of leptin, which could also contribute to loss of bone mass [19,20]. Low HDL levels, high TG levels and elevated blood pressure are associated with the development of arteriosclerosis and have been suggested to promote the loss of BMD, as small arteries, which provide blood supply for bone metabolism, are affected [21,22,23,24,25]. …”
Section: Introductionmentioning
confidence: 99%